Mass spectrometric analysis of oligoribonucleotides of total yeast RNA - Tkachuk, Z.Yu.; Levchenko, S.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
To find out the composition of oligoribonucleotides of total yeast RNA ingredient that is present in antiviral drug Nuclex with multiple actions and immunomodulator Nucleinat, are liquid chromatography and mass spectrometry MALDI-Tof-Tof methods were used for ribonucleotides analysis. It was shown that the total yeast RNA contains three main fractions: the first one — from 2 to 4 nt, the second one — from 4 to7 nt and the third one — from 10 to 15 nt. It is shown that the total yeast RNA contains different oligoribonucleotides with lengths from 4 to 15 nt.